Local exome sequences facilitate imputation of less common variants and increase power of genome wide association studies. - Peter K Joshi; James Prendergast; Ross M Fraser; Jennifer E Huffman; Veronique Vitart; Caroline Hayward; Ruth McQuillan; Dominik Glodzik; Ozren Polašek; Nicholas D Hastie; Igor Rudan; Harry Campbell; et al. (PLoS ONE)
The analysis of less common variants in genome-wide association studies promises to elucidate complex trait genetics but is hampered by low power to reliably detect association. We show that addition of population-specific exome sequence data to global reference data allows more accurate imputation, particularly of less common SNPs (minor allele frequency 1-10%) in two very different European populations. The imputation improvement corresponds to an increase in effective sample size of 28-38%, for SNPs with a minor allele frequency in the range 1-3%.